1979
DOI: 10.1093/jnci/63.3.843
|View full text |Cite
|
Sign up to set email alerts
|

Partial Deletion of Chromosome #2 in Myelocytic Leukemias of Irradiated C3H/He and RFM Mice2

Abstract: Chromosomes of mouse myelocytic leukemias that developed in 7 irradiated mice, 3 C3H/He males, 1 RFM female, and 3 RFM males were analyzed with chromosome-banding techniques. Chromosomes No. 2 were partially deleted in 6 of the 7 mice. Although the deleted No. 2 chromosomes varied in size in the 6 mice, one common characteristic was noted in all these deletions: A segment lying between a certain band in the region 2C and a band in the region 2E, including the whole region 2D, was missing. Another consistent ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…It has been known for years by the present investigators that four strains of mice developed an increased incidence of acute myelogenous leukemia after exposure to ionizing radiation (50)(51)(52)(53)(54). The RFM strain is less desirable because of expense and it has a high spontaneous incidence of acute myeloblastic and other leukemias.…”
Section: Discussionmentioning
confidence: 97%
“…It has been known for years by the present investigators that four strains of mice developed an increased incidence of acute myelogenous leukemia after exposure to ionizing radiation (50)(51)(52)(53)(54). The RFM strain is less desirable because of expense and it has a high spontaneous incidence of acute myeloblastic and other leukemias.…”
Section: Discussionmentioning
confidence: 97%
“…For many years, it has been known that irradiated mice frequently develop AML after a long latent period; nearly all of these tumors contain an interstitial deletion of one copy of chromosome 2 that includes the PU.1 gene (7)(8)(9)(10)(11)(12). Adams' group evaluated the sequence of the residual PU.1 allele in AML tumors arising in irradiated mice and found that 87% contained mutations in the ETS-binding domain located within exon 5 (6).…”
mentioning
confidence: 99%
“…Leukemia cells were isolated from leukemic individuals and were characterized histochemically [9]. After 5 cycles of in vivo passage for stabilization of histochemical phenotype [9] and chromosome number [10], leukemic cells were stored in liquid nitrogen. The frozen cells were thawed, washed with saline and injected intravenously (1-I0× 104 cells per mice) into 6-week-old male C3H/He mice, and after 24 weeks, proliferated leukemia cells were isolated from the spleen of the leukemia mice.…”
Section: Leukemia Cells and Dna Preparationmentioning
confidence: 99%
“…To confirm this supposition as well as to study the chronic effects of radiation, we used radiation-induced acute myeloid leukemia cells from the C3H/He mouse for analysis. Approximately 20-30% of whole-body X-irradiated C3H/He mice develop acute myeloid leukemia within 2 years with chromosomal aberrations [9,10]. Each leukemia cell strain from different individuals should be an 'independent' leukemia since they became tumorigenic by separate processes.…”
mentioning
confidence: 99%